Gender and Roasting: Comparative Analysis of Negotiation and Evaluation in Indonesian Comedians - Ariel Achmad Pramudya; Harni Kartika Ningsih (Green Publisher Indonesia, 2026)
This study aimed to investigate roasting as an interactive humor genre by examining differences in exchange structures and evaluation strategies between male and female comedians. The study employed two interpersonal systems of discourse semantics from Systemic Functional Linguistics—Negotiation and Appraisal. The data were drawn from an Indonesian political-themed roasting show featuring two comedians delivering humor related to Indonesian presidential election issues. The findings revealed several key results. First, roasting as a comedic genre can be realized through either immediate or delayed success, where joke effectiveness is indicated by different evaluative responses. Failure in delivering jokes is indicated by audience silence. Second, there are differences in the choice of evaluation strategies between male and female comedians. The male comedian tended to use a direct emotional strategy targeting concrete subjects, which resulted in more immediate comedic success. In contrast, the female comedian employed an analytical and layered strategy that produced more sophisticated humor, although it carried a higher risk of failure. These differences highlight distinct gendered approaches to comedic performance and humor construction